Testing The Compressive Strength Of Concrete With The Utilization Of Rice Husk Ash And Palm Fiber - Bhakti Aslon, Muh. Wonua; Lakawa, Irwan; Sulaiman, Sulaiman; Hawa, Sitti (Universitas Sulawesi Tenggara, 2023)
Development in the field of structure is currently progressing very rapidly in various field so that concrete is one of the choices as a structural material in building construction, basically concrete is made by mixing portland cement, coarse aggregate, fine aggregate, and water as a binder for these materials. Due to the development of the issue of current resource limitations, the prevention is by innovating the manufacture of concrete using palm fiber waste as an added ingredient from sand and rice husk ash waste as an added ingredient from cement. The purpose of study was to (1) analyze the compressive strength of concrete with variations ini rice husk ash and palm fiber (2) analyze the addition of rice husk ash and palm fiber with different mixture variations that could affect the compressive strength of concrete. The result showed that normal concrete with an average compressive strength of 24.20 MPa and an increase in compressive strength with a mixture of 0.5% palm fiber and 5% rice husk ash with an average strength of 25.90 MPa without using superplasticizer, if the variation mixture exceeding the mixed variation of 0.5% palm fiber and 5% rice husk ash will deacrease